2021
DOI: 10.1186/s43166-020-00055-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid with clinical and radiological severity of knee osteoarthritis in non-gouty patients

Abstract: Background A growing body of evidence suggested that uric acid (UA) may contribute in the pathways underlying osteoarthritis (OA) pathogenesis; however, studies that investigated the relationship between UA and OA emerged inconclusive results. The purpose of the study was to explore the association of serum uric acid (sUA) levels with clinical severity, radiological severity of knee osteoarthritis (KOA) based on Kellgren-Lawrence (KL) grading system, and MRI changes in non-gouty patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Interestingly, this connection was not observed in male patients. These results highlight the importance of understanding the gender-specific nature of the relationship between uric acid and KOA severity [28].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, this connection was not observed in male patients. These results highlight the importance of understanding the gender-specific nature of the relationship between uric acid and KOA severity [28].…”
Section: Discussionmentioning
confidence: 80%
“…This disparity emphasizes the potential role of uric acid in the development of KOA and provides valuable insights into its relevance for understanding the underlying mechanisms of the disease. A study by Bassiouni et al (2021) reported that there is a strong link between uric acid levels and the severity of KOA in female patients. Interestingly, this connection was not observed in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 3099 individuals aged 65 and older, hyperuricemia was associated with hand OA in women, and hyperuricemia was significantly related to knee OA in men [ 21 ]. One study focused on the association of serum uric acid with the clinical and radiological severity of knee OA and found that the group with higher serum uric acid exhibited more severe changes, including a higher frequency of Kellgren-Lawrence (KL) grade 4, grade 4 osteophytes, and narrower joint space width (JSW) [ 14 ]. Our findings revealed that in patients with OA, hyperuricemia was associated with an increased risk of all-cause mortality and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia has also been found to be associated with a higher prevalence of hand OA [ 13 ]. In a study specifically examining knee OA, patients with higher serum uric acid levels displayed more severe symptoms and radiological signs of knee OA, including more severe pain, stiffness, and function scores [ 14 ]. However, there is a lack of research exploring the relationship between hyperuricemia and the overall mortality risk or the risk of CVD death in patients with OA from the literature search by the authors.…”
Section: Introductionmentioning
confidence: 99%